Meeting scheduler with secured privacy web application - Lok, Samantha Tian Wen (2023)
The scheduling and management of meetings in universities pose significant challenges. Therefore, a meeting scheduler web application with secured privacy has been proposed to address these issues. The system is developed system to automate the information systems for an arrangement of meeting between users alternatively. The system includes an integration data set as the Google authentication for users to give their credentials to allow the system to extract the information given. The system also developed to evaluate the use of CRUD (Create, Read, Update, Delete) in the web-based information systems as it is crucial that the systems extracted precise and accurate data. To develop the meeting scheduler web application with secured privacy, technologies such as Python, HTML, MongoDB, CSS, and JavaScript were used. The proposed system addresses the limitations of manual meeting management and suggests solutions to overcome them.